OCMS as Third Space - Behera, Marina Ngursangzeli (Transformation, 2024)
This article analyse the work of the Oxford Centre for Mission Studies (OCMS) through the lens of Bhabha's ‘third space’, highlighting its role in the global mission debate and its influence on the integration of non-Western theological perspectives within Western academia. The OCMS, founded with a vision to decolonise theology and create a space for voices from the majority world, has evolved as a hybrid institution bridging various divides–between evangelical and ecumenical missions, majority world and Western academia as well as mission theologians and practitioners. This ‘third space’ serves as a unique platform where global South scholars can engage in rigorous mission research while remaining contextually grounded. By facilitating this dynamic exchange, OCMS contributes to the decolonisation of theological education and the production of knowledge that resonates globally.